Pengaruh Upah Minimum dan Investasi Pada Permintaan Tenaga Kerja di Provinsi Bali - Mahayana, I Made Alit; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Minimum wage and investment has an important role in creating the labor demand. Increasing minimum wage by government and investment will determine the labor demand and unemployment of one region. In order to handle unemployment problem, government need to balance the supply of labor and the availability of job. This research objective is to analyze the impact of increasing in minimum wage and investment toward labor demand in Bali Province in 1993-2012 periods. Analysis method that used in this study is multiple regression method. The result shows, in every 1 percent increase in minimum wage will lowered the labor demand by 18,19 percent. Meanwhile, for every 1 percent increase in investment will increase the labor demand by 1,15 percent. To handle the unemployment, which creates by 1 percenr increase of minimum wage, the government has to increase the investment at least 1,15 percent. Furthermore, in order to handle the unemployment in 2013, Bali economy has to invest at least Rp. 195 billion.
Keywords: Labor; Minimum Wage; Investment; Labor Demand; Unemployment